2014
DOI: 10.1007/s00125-014-3389-3
|View full text |Cite
|
Sign up to set email alerts
|

Association of urinary KIM-1, L-FABP, NAG and NGAL with incident end-stage renal disease and mortality in American Indians with type 2 diabetes mellitus

Abstract: Aims/hypothesis Kidney injury molecule 1 (KIM-1), liver fatty acid-binding protein (L-FABP), N-acetyl-β-D-glucosaminidase (NAG) and neutrophil gelatinase-associated lipocalin (NGAL) are urinary biomarkers of renal tubular injury. We examined their association with incident end-stage renal disease (ESRD) and all-cause mortality in American Indians with type 2 diabetes. Methods Biomarker concentrations were measured in baseline urine samples in 260 Pima Indians who were followed for a median of 14 years. HRs w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
95
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 88 publications
(103 citation statements)
references
References 45 publications
6
95
2
Order By: Relevance
“…For example, earlier work in the ARIC Study showed that urinary NGAL but not KIM-1 was associated with higher risk of stage 3 CKD (6), whereas in the Multi-Ethnic Study of Atherosclerosis, higher urinary KIM-1 but not NGAL was associated with increased incident stage 3 CKD and rapid eGFR decline (5). Similar to the prior study in the ARIC Study, in Pima Indians with type 2 diabetes, NGAL/Cr but not KIM-1/Cr was associated with increased ESRD risk over 13.5 years median follow-up (15). In the Chronic Renal Insufficiency Cohort (CRIC), higher absolute NGAL levels were associated with a higher risk of progressive CKD, defined as incident ESRD or halving of eGFR; L-FABP, NAG, and KIM-1 were not measured in that report (8).…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…For example, earlier work in the ARIC Study showed that urinary NGAL but not KIM-1 was associated with higher risk of stage 3 CKD (6), whereas in the Multi-Ethnic Study of Atherosclerosis, higher urinary KIM-1 but not NGAL was associated with increased incident stage 3 CKD and rapid eGFR decline (5). Similar to the prior study in the ARIC Study, in Pima Indians with type 2 diabetes, NGAL/Cr but not KIM-1/Cr was associated with increased ESRD risk over 13.5 years median follow-up (15). In the Chronic Renal Insufficiency Cohort (CRIC), higher absolute NGAL levels were associated with a higher risk of progressive CKD, defined as incident ESRD or halving of eGFR; L-FABP, NAG, and KIM-1 were not measured in that report (8).…”
Section: Discussionsupporting
confidence: 54%
“…Urinary biomarkers were indexed to urinary creatinine in our primary analyses for consistency with other analyses of urinary biomarkers in the CKD Biomarkers Consortium (15). KIM-1 indexed to creatinine (KIM-1/Cr), NAG/Cr, and NGAL/Cr were evaluated categorically as quartiles and continuously with a log 10 transformation to account for their skewed distributions.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…In a cross-sectional study, we previously found urinary adiponectin excretion to be positively related to albuminuria in type 1 diabetes [9]. Moreover, prospective studies have shown that high urinary adiponectin is associated with the development of end-stage renal disease [10,11]. The association between these urinary markers, incident CVD and all-cause mortality, when adjusted for levels of Nterminal pro-brain natriuretic peptide (NT-proBNP) and the coronary artery calcium (CAC) score is, however, unknown.…”
Section: Introductionmentioning
confidence: 94%
“…1. Based on their graphical distribution and a significant result in the ShapiroWilk test (p ≤ 0.001; indicating non-normal distribution), both biomarkers were log-transformed using log 10 .…”
Section: Statistical Analysesmentioning
confidence: 99%
“…All the data mentioned above indicated that tubular damage is common at the early stage of type 2 diabetic patients and urinary NGAL, KIM-1 and NAG could be early promising biomarkers for renal impairment in DN patients. A recent study showed that urinary KIM-1, NAG and NGAL were not only urinary biomarkers of renal tubular injury, but also showed that median concentrations of KIM-1/Cr, NAG/Cr and NGAL/Cr were highest in diabetic patients with macroalbuminuria and NGAL/Cr was positively associated with ESRD and mortality (Fufaa et al 2014). …”
Section: Ngal Kim-1 and Nagmentioning
confidence: 99%